A 17-Year-Old Female with Systemic Lupus Presents with Complex Movement Disorder: Possible Relationship with Antiribosomal P Antibodies. (8th May 2013) - Özcan, Muhammed Emin; Altınöz, Meriç Adil; Karadeli, Hasan Hüseyin; Asil, Talip; Koçer, Abdulkadir
Abstract : Complex movement disorder is a relatively rare presentation of neurolupus. Antiphospholipid antibodies are associated with movement disorders likely via aberrant neuronal stimulation. Antiribosomal P antibodies have been previously associated with neuropsychiatric disorders but their correlation with movement disorder was not previously established. Our case report involves a 17-year-old Caucasian female patient positive for only antiribosomal P antibody and lupus anticoagulant who presented with a sudden onset of complex movement disorder. After complete cessation of physical signs with olanzapine, anticardiolipin and anti- β 2 glycoprotein I antibodies became positive which indicates a likely discordance between movement disorder and antiphospholipid antibodies. This also indicates a potential causal role of antiribosomal P antibodies in inducing movement disorder.